Condição de saúde bucal e qualidade de vida de pacientes com Leucemia Mieloide Crônica em um Cenro de Referência em Hematologia no Amazonas - Bittencourt, Augusto Arcemiro (2022)
Chronic Myeloid Leukemia (CML) is a myeloproliferative disease characterized by the presence of the Philadelphia chromosome (Ph). The management and treatment of patients with CML should be carried out by a multidisciplinary team, including a dental surgeon, whose knowledge of the oral condition profile of these patients becomes important for a better performance in promoting their oral health and consequently also impacting directly or indirectly. indirectly on the quality of life of these patients. Objective: To evaluate the oral health status and quality of life of patients with CML diagnosed at a hematological referral center in Amazonas. Methodology: This is a clinical, cross-sectional descriptive/analytical study that evaluated oral manifestations (OM), DMFT, plaque index (PI), probing depth (PD), Clinical attachment loss (CAL), bleeding on probing (BoP), periodontal diagnosis and oral health-related quality of life (OHIP-14), in patients with CML up to 3 years of imatinib use. Results: A total of 36 patients were evaluated, 52.8% of whom were male, the median age was 57,5 years, 94% had basic education and 72.2% had an income ≤ 239 dollar. The frequency of OM was 5.5% (n=2), being an ulcerated lesion and a pedicular lesion, DMFT index: 9,99, being 17% (n=6) of the total edentulous patients (17%) and 77.7% with dental caries disease (n=28). Of the patients subject to periodontal evaluation (n=30), the following results were observed: PI: 57.5% (±27.37), CAL 3.10 mm (± 0 .35), PD 2.13mm (± 0.28), BoP: 49.4% (±28.92), and predominantly diagnosis of gingivitis 83.3%, being 80% generalized gingivitis and 71.4% with reduced periodontium. The assessment of the impact of weak OHIP-14 on quality of life at 8.9% (n=32). Conclusion: The condition of patients with CML using imatinib up to 3 years was satisfactory considering the high caries and dental caries, although a low frequency of tissue changes that indicate the need for surveillance in this study, which indicates the need for dental surveillance in this population